Biodegradation of Anionic Surfactants in River Water - TAGAWA, Mieko; GOTOH, Keiko (Journal of Home Economics of Japan, 2001)
The rates of biodegradation of anionic surfactants, linear alkylbenzenesulfonate (LAS), alkyl sulfate (AS), alkyl ether sulfate (AES), α-olefinsulfonate (AOS) and alkylcarbonate (Soap), were determined by a river water die-away test. River water was obtained from the basins of the Yodo River and the Yamato River. The biodegradability of the surfactants was evaluated by the methylene blue activity. The biodegradation rate was small for LAS, and large for both AS and Soap. The rate of biodegradation was found to be enhanced in polluted river water at high water temperature. With increasing surfactant concentration, the biodegraded amount of the surfactant increased, although the biodegradation rate decreased.